2000
DOI: 10.1177/004051750007000111
|View full text |Cite
|
Sign up to set email alerts
|

Durable Flame Retardant Cotton Fabric Prepared by Partial Pyrophosphorylation and Metal Complexation

Abstract: In order to prepare durable flame retardant cotton, mercerized cotton fabric is treated with orthophosphoric acid at 140°C or pyrophosphoric acid at 110°C, followed by metal-complexation. The LOI (limited oxygen index) values of the pyrophosphorylated cotton fabrics are higher than those of orthophosphorylated fabrics; the pyrophosphorylated fabric treated with Ni

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The phosphorylation of starch with sodium trimetaphosphate was also performed by reactive extrusion allowing higher degrees of substitution. 111,112 Sekiguchi et al 62 showed that the phosphorylation of cellulose in DMF with H 4 P 2 O 7 was more efficient when the reaction was performed in the presence of phosphoric acid and-or cyanoguanidine. Phosphate derivatives of chitosan may be obtained by interpolymer linkage of chitosan with sodium tripolyphosphate or polyphosphate.…”
Section: Polysaccharide Phosphorylation With Polyphosphorus Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of starch with sodium trimetaphosphate was also performed by reactive extrusion allowing higher degrees of substitution. 111,112 Sekiguchi et al 62 showed that the phosphorylation of cellulose in DMF with H 4 P 2 O 7 was more efficient when the reaction was performed in the presence of phosphoric acid and-or cyanoguanidine. Phosphate derivatives of chitosan may be obtained by interpolymer linkage of chitosan with sodium tripolyphosphate or polyphosphate.…”
Section: Polysaccharide Phosphorylation With Polyphosphorus Compoundsmentioning
confidence: 99%
“…For instance, the use of polyphosphorus or alkyl chlorophosphate compounds as phosphorylating agents has been developed in the field of textile chemistry in order to prepare fireproof fabrics. 62 Phosphorylated compounds are char-forming materials; they prevent combustion and delay the spread of the fire after ignition. During combustion, phosphorus generates a polymeric form of phosphoric acid.…”
Section: Applications Of Phosphorylated Polysaccharidesmentioning
confidence: 99%
“…Giraud 4 , et al studied the flame behaviour of cotton coated with polyurethane containing micro encapsulated flame-retardant agent. Sekiguchi 5 worked for durable flame-retardant cotton fabric prepared by partial phosphorylation and metal complexation.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, it should be noted that the synthesis of phosphorylated cellulose requires high temperatures and a lengthy process before it can be used as an additive. 17 Thus, the utilization of commercial flame retardants to fabricate flameretardant lyocell fiber through the blend method has received relatively little attention to date.…”
Section: Introductionmentioning
confidence: 99%
“…To address these concerns, researchers have turned to phosphorylated microcrystalline cellulose as an alternative for the production of flame‐retardant lyocell fiber through a cost‐effective blend strategy 16 . However, it should be noted that the synthesis of phosphorylated cellulose requires high temperatures and a lengthy process before it can be used as an additive 17 . Thus, the utilization of commercial flame retardants to fabricate flame‐retardant lyocell fiber through the blend method has received relatively little attention to date.…”
Section: Introductionmentioning
confidence: 99%